Nilai pendidikan karakter dalam proses asah asih asuh Anak majikan studi kasus pekerja migran di Hongkong - Nurbaya, St.; Marzuki, Marzuki (Jurnal Pendidikan Karakter, 2023)
The purpose of this study is to describe the value of character education that is transformed by YouTuber MAS in the process of teaching, caring, and caring for the employer's children which is broadcast on the YouTube channel. The formulation of the problem addressed is what character education values are transformed by Markhatin Solikha to his foster children GNV. The research method is a content analysis method that specifically analyzes communication events (CA). The focus of this research analysis is the communication events contained in the video- Markhatin MAS videos on his YouTube channel. The type of data is in the form of conversations or dialogues between caregivers and their foster children which are transcribed in the form of data cards. The unit of analysis is sentences, phrases and/or clauses as well as spoken words and behavior in the video that contain character education values. The main instrument is researchers who focus on observation activities in the form of observing notes. The conclusion of the research results found is the values of character education found are the values of honesty, religion, tolerance, responsibility, independence, creativity.